In-depth control over football players' speed abilities at sport specialization stage - Zakharova, A. V.; Mekhdieva, K. R.; Kondratovich, S. V.; Timokhin, V. E. (Theory and Practice of Physical Culture, 2020)
Objective of the study was to analyze benefits of a comprehensive speed qualities test set and individual speed qualities progress profiling system for the 14-15 year old football players. Methods and structure of the study. The laboratory test toolkit included: a psychophysiological test used to obtain the central nervous system functionality rates. The pedagogical test toolkit included: 30m run from standing start, flying ball strike, standing long jump and football T-test ? speed run with changing directions. Sampled for the study conducted in March 2019 were 24 football players of 2004 of birth (body length - 170.83±6.13 cm, body weight - 59.85±10.67 kg, maximum oxygen consumption - 51.93±5.52 ml/kg/min). The athletes and their parents were informed in detail on the ongoing research goals, objectives and methods and gave a written consent for the study and publication of the data obtained. The work was carried out in accordance with the WMA Declaration of Helsinki. The laboratory tests were conducted in the laboratory "Technologies of Sports Rehabilitation and Selection" of the Common Use Center of Ural State University, field tests - on the grass pitch of the Specialized Children and Youth Sports School of the Olympic Reserve "VIZ".